Unregulated disinfection By-products in drinking water in Quebec: A meta analysis. (1st October 2018) - Chhipi-Shrestha, Gyan; Rodriguez, Manuel; Sadiq, Rehan
Abstract: Disinfection by-products (DBPs) are formed primarily by the reaction of natural organic matter and disinfectants. DBPs that are not regulated are referred to as unregulated DBPs (U-DBPs) and they are in majority in total DBPs. U-DBPs can be more toxic than regulated DBPs. U-DBPs such as haloacetonitriles (HANs), haloacetonitriles (HKs) and halonitromethanes (HNMs) are widely present in drinking water supplies in different regions of the world. This study investigated the occurrence of U-DBPs and their variability in drinking water in the Province of Quebec (Canada), using the water quality database of 40 municipal water systems generated by our research group. The concentrations of HANs, HKs, and their compounds, including chloropicrin (CPK), were highly variable in different water systems in Quebec. The concentration range of these U-DBPs is in line with drinking water concentration ranges in different regions of the world. Factors such as system size, water source, season, pH, total organic carbon content, free residual chlorine and disinfectant types cause significant variations in the concentrations of HANs, HKs and their constituent compounds, including CPK, in drinking water in Quebec. This information is valuable for decision making concerning source water selection, water distribution planning, water treatment plant design including disinfection, and overall drinking water quality management related to U-DBPs. Moreover, U-DBPs and regulated DBPs are strongly correlated, although the degree of correlation can vary with water source, system size and season, indicating that regulated DBPs can be used as surrogates of U-DBPs. Highlights: Analyzed drinking water quality data of 40 municipal water systems of Quebec. Haloacetonitriles, haloketones and chloropicrin concentrations were highly variable. System size, water source, season, TOC, and disinfectants affect unregulated DBPs. High correlation between regulated and unregulated DBPs (U-DBPs). Water source, system size and season affect the degree of correlation.